Multidisciplinary 3D geological-petrophysical reservoir characterization of Abu Sennan Field, Abu Gharadig Basin, Egypt - Mohamed Mamdouh; Adel Ali Ali Othman; Taher Mostafa (Scientific Reports)
Abstract Reservoir heterogeneity within the Cretaceous Abu Roash and Bahariya formations of the Abu Sennan Field (Western Desert, Egypt) presents a significant challenge to hydrocarbon prospect evaluation. This study applies an integrated approach combining well logs from four wells, core analysis, and 2D seismic data to assess reservoir quality and structural framework. The workflow includes: (1) petrophysical evaluation to quantify shale volume (Vsh), effective porosity (ϕe), and hydrocarbon saturation (Sh) across five reservoir intervals—Abu Roash C (net pay 1–32.5 m, Vsh 29–35%, ϕe 19–29%, Sh 52–67%), Abu Roash D (7–10.5 m, Vsh 2–13%, ϕe 17–23%, Sh 60–90%), Abu Roash E (3.4–48.6 m, Vsh 20–30%, ϕe 18–24%, Sh 62–76%), Abu Roash G (3–12.5 m, Vsh 11–18%, ϕe 22–24%, Sh 58–73%), and Bahariya (2.5–52.5 m, Vsh 17–27%, ϕe 15–26%, Sh 46–77%); (2) seismic interpretation identifying a NW–SE-trending horst structure bounded by E–W and NNW–SSE fault systems, which compartmentalize the reservoirs; and (3) 3D static modeling to visualize the distribution of facies, porosity, and saturation. The results highlight the AR-D-01 structural closure within the Abu Roash D member as a high-potential prospect, featuring dissolution-enhanced vuggy porosity (ϕe 17–24%) and elevated hydrocarbon saturation (Sₕ 60–90%) corroborated by depth structure maps and petrophysical property models. Overall, the study demonstrates that fault-controlled diagenesis improves reservoir quality in grainstone facies, offering a reliable framework for targeted hydrocarbon exploration in heterogeneous systems.